Flexible work and the family - Abendroth, Anja-Kristin; Lükemann, Laura (Contemporary perspectives on family research ;, 2023)
National strategies with the aim of facilitating a better work-family balance have increased pressure on work organizations to offer arrangements that are more family-friendly. Flexible work, such as telework or flexitime, has been argued to facilitate a better integration of work and family responsibilities, and to provide protections from career penalties to care. The spread of digital technologies has further facilitated the flexible execution of work tasks, a phenomenon that has escalated more recently due to the global COVID-19 pandemic. Within this context, where flexible work has become more widespread than ever before, Flexible Work and the Family provides a wide range of insights into current developments in the study of flexible work. Demonstrating both the facilitators and the barriers to a positive work-home environment, chapters delve into the relationship between working from home and family in light of the pandemic, as well as gender, parenthood, and status-specific patterns of the interrelation between flexible work and the family. Finally, studies from a linked-lives perspective show how flexible work impacts employees' partners and parenting behaviour. Building upon the recent global escalation of the remote work phenomenon, Flexible Work and the Family provides timely insights into flexible work's implications for the increasingly blurred work-life divide.